Recent developments and new challenges in commodity markets and policy options for commodity-based inclusive growth and sustainable development (UN New YorkUS, 2013)
Reviews recent developments in key commodity markets and analyses the underlying factors contributing to price volatilities in 2012.
Note by the UNCTAD Secretariat.